2015
DOI: 10.1162/neco_a_00703
|View full text |Cite
|
Sign up to set email alerts
|

What Can Neuromorphic Event-Driven Precise Timing Add to Spike-Based Pattern Recognition?

Abstract: This letter introduces a study to precisely measure what an increase in spike timing precision can add to spike-driven pattern recognition algorithms. The concept of generating spikes from images by converting gray levels into spike timings is currently at the basis of almost every spike-based modeling of biological visual systems. The use of images naturally leads to generating incorrect artificial and redundant spike timings and, more important, also contradicts biological findings indicating that visual pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…or asynchronous event-based (Akolkar et al, 2015) visual information. Works about natural image statistics (Hyvarinen et al, 2009) showed that similar decompositions of visual information emerge naturally from independent component analysis applied on patches collected on natural images.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…or asynchronous event-based (Akolkar et al, 2015) visual information. Works about natural image statistics (Hyvarinen et al, 2009) showed that similar decompositions of visual information emerge naturally from independent component analysis applied on patches collected on natural images.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…s −1 , i.e., inversely close to the temporal precision of the visual events, estimated over 1 ms (cf. Akolkar et al, 2015). Motions with intensities less than v min are then discarded: they are assumed as belonging to static or faraway objects in the background visual scene.…”
Section: Motion-based Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies process the data stream on an event-by-event basis [16][17][18][19][20][21][22][23][24][25][26][27][28][29], with the timing of an event determining its relevance to an internal model. Some event-based studies accumulate event activities and then decay them as time passes [30][31][32][33][34].…”
Section: Processing the Temporal And Spatial Information In Event-basmentioning
confidence: 99%
“…• SNNs [34], with event-driven convolutional neural networks [8,31], or with leaky integrate-and-fire neurons [32,50] in deep belief networks [33] • Event-based iterative closest point [30,48] Continued on next page [26,35,39], for occlusion of multiple objects [83] • Self-organising map [60] • Spike-based vector integration to end point [25] Event by event, with a temporal gradient for each event…”
Section: Framesmentioning
confidence: 99%